Analysis of the Mathematical Communication Skills of Grade XII Vocational High School Students on Linear Programming Material - Siti Khotijah; Dwi Rahmawati; Sudarman Dami (LifeSciFi, 2026)
The low level of students’ mathematical communication skills in mathematics learning, particularly in linear programming topics, remains a significant concern. This issue is critical because linear programming requires students to express, represent, and justify mathematical ideas systematically in both written and visual forms. The study aimed to analyze the mathematical communication skills of grade XII vocational high school students based on indicators of oral and written communication, mathematical representation, and reasoning and symbolic thinking. This study employed a qualitative method with a descriptive approach involving 12 students selected purposively. Data were collected through essay tests and in-depth interviews and analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings revealed that students’ mathematical communication skills were still predominantly in the low category, with 6 students categorized as low, 4 as moderate, and 2 as high. Students in the high category were able to construct mathematical models and explain solution procedures systematically, whereas students in the low category experienced difficulties in using symbols, representations, and logical reasoning. The study concludes that students’ mathematical communication skills are not yet optimal; therefore, more active, communicative, and contextual learning strategies are needed to improve students’ ability to express mathematical ideas systematically.